Agency and the Adagio: Mimetic Engagement in Barber's Op. 11 Quartet - Matthew Baileyshea (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Samuel Barber’s Adagio for Strings (1936) is undoubtedly the most famous elegiac work of the twentieth-century. We know it from movies, television, and highly publicized memorial services. Yet the music was originally written as the second movement of Barber’s string quartet, op. 11, with a number of interesting connections to the outer movements. This article highlights several recurring gestures throughout op. 11 that suggest the will of an individual “agent” struggling against gravity and weight. It proposes a broad, multi-movement narrative that draws together the three movements with a special focus on mimetic engagement, leading-tone resolution, and the quest for major-mode closure.